FREQUENCY OF ROTAVIRUS INFECTION IN CHILDREN UNDER 2 YEARS OF AGE PRESENTING WITH DIARRHEA AT TERTIARY CARE HOSPITAL - Iqbal, Sahar; Gul, Huma; Mujtaba, Muhammad; sherazi , Farida; Jehanzeb, Sadia; Naz, Irum (Khyber Journal of Medical Sciences, 2025)
Objective: To find out the frequency of rotavirus infection in children below 2 years of age presenting with diarrhea at Northwest General Hospital, Peshawar. Methods and material: This cross-sectional study was conducted in the Department of Pediatrics of Northwest General Hospital Peshawar from 10th August 2020 to 10th February 2021. By non-probability convenience sampling technique taking a 95% confidence interval, 5% margin of error, and population of 24% the calculated sample size was 281. The data was analyzed by SPSS V 23.0. Results: A total of 281 cases were analyzed for this study. After analysis, the mean age was calculated as 10.960±3.93 months. The mean weight was 9.253±1.54 Kgs the mean duration of diarrhea was reported as 8.409±1.99 days. 53(18.9%) out of 281 were reported as positive for rotavirus infection. Among 281 only 20 patients which is 7.1% of the sample size got vaccinated against the Rotavirus in our study. Taking the p-value below 0.05 as significant rotavirus infection has shown significance with exclusive breastfeeding and their vaccination history. Conclusion: Rotavirus is one of the major causes of acute gastroenteritis. The rotavirus has shown a significant relationship between vaccination against rotavirus and exclusive breastfeeding with a p-value of less than 0.05.